Physical education teacher skills in preparing HOTS lesson plans and their contribution to teaching performance - Hardiansyah, Sefri; Blegur, Jusuf (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2024)
Background: Higher-order thinking skills (HOTS) are 21st-century thinking skills needed by students to survive the demands of the current era. However, the problem is that teachers often do not optimally include HOTS in the lesson plan and the implementation of learning. Research Objective: This study aimed to investigate the relationship between the teacher's skill in preparing HOTS lesson plans and the teacher's performance in applying them to physical education. Methods: This type of research is correlational using two research variables: the teacher's skills in preparing HOTS lesson plans and teaching performance. The participants were 28 physical education teachers (men = 21, women = 7) who participated in the Teacher Professional Education Programme at Universitas Negeri Padang in 2022. The HOTS lesson plan data and teacher teaching videos were taken from the documented performance test results (PDF files and teaching videos). Data analysis used regression with the help of SPSS version 25. Findings/Results: The results showed that α < 0.05 (0.007) with a regression value of 2.923 means that the teacher's skills in preparing HOTS lesson plans are positively determined by their performance in teaching HOTS to students. The contribution made by the teacher's ability to prepare HOTS lesson plans to teacher teaching performance is 24.70%. Conclusion: Teachers who can prepare a good HOTS lesson plan can provide a guarantee for their HOTS teaching performance. Thus, the more detailed the teacher formulates the goals, objectives, activities, media, and HOTS assessments, the more it helps them determine their teaching performance that encourages their students' HOTS.